Spatiotemporal Demographic Trends and Land Use Dynamics of Metropolitan Lahore - Farhat, Komal; Waseem, Liaqat Ali; Khan, Ashfak ahmad; Baig, Shahbaz (Journal of History Culture and Art Research, 2018)
The research aims to investigate the pace of rapid urbanization in the mega cities of developing countries. These are facing unprecedented population growth and unplanned rapid urbanization. Pakistan is considered as most urbanized country in Asia. Keeping in view the unplanned urbanization and rapid population growth, study was conducted in metropolitan Lahore which is the second mega city of Pakistan with 82% of urban population to examine the spatiotemporal demographics and land use changes. The secondary data about temporal demographic trends was collected from different government departments and their reports like, Lahore Development Authority (LDA), Cantonment Board Lahore (CBL) Bureau of Statistics Punjab (BOS), Punjab Development Statistics (PDS) and District Census Reports (DCR) Lahore. Spatial primary data was created by geospatial techniques to assess the land use dynamics. 2000 to 2015 Landsat images of 8MSS and 5TM were classified through supervised classification for land use land cover change detection. In-depth interviews were conducted from LDA officials to verify and interpret the temporal population trends and town wise land use land cover changes. Research findings revealed that population of Lahore is continuously rising since 1951 to date due to rural urban migration. The gradual population increase is enhancing civic population density and immense urban sprawl. The research in line with the above-mentioned factors gives the spatial presentation of urban land use land cover changes from 2000 to 2015. The stakeholders should check the alarming speed of urbanization and balance the population agglomeration and land use balance to sustain the city. These perspectives will be helpful to find new way for future project planning and prioritization of the mega cities.